Leptospira interrogans serovar Hardjo seroprevalence and farming practices on small-scale dairy farms in North Eastern India; Insights gained from a cross-sectional study - Leahy, E.; Shome, R.; Deka, Ram Pratim; Grace, Delia; Sahay, S.; Lindahl, Johanna F. (MDPI, 2021)
Leptospirosis is a zoonotic disease of major public health concern in India. Bovines play an important role in maintaining and transmitting this disease and proximity between dairy cows and humans makes the dairy cow-human nexus a transmission route of public health interest, yet one currently under-examined in North Eastern India. We report a cross-sectional survey carried out on small-scale dairy farms in the states of Assam and Bihar in North Eastern India investigating seroprevalence for Leptospira interrogans serovar Hardjo, the most common pathogenic serovar reported in cattle worldwide. Higher seroprevalence was reported on dairy farms in Bihar 4.5% (95% CI 2.6–7.5%) than in Assam 1.2% (95% CI 0.42–3.6%), but overall seroprevalence levels were low. The study is the first indication of leptospirosis circulating in small-scale dairy farms in these states. To correlate farming practices with zoonotic risk, we combined results from a dairy farmer questionnaire with cow seroprevalence. However, low seroprevalence levels found in this study made the identification of risk factors difficult. Nevertheless, poor farming practices around hygiene and biosecurity on dairy farms have been highlighted. Implementing simple measures could mitigate environmental contamination, and therefore, reduce the risk of Leptospira interrogans, and other zoonoses transmission, at the animal-environment-human interface.